Effect of milling time and clay content on the thermal stability of polyethylene‐clay nanocomposite. Issue 3 (11th August 2014) - Abareshi, Maryam; Zebarjad, Seyed Mojtaba; Goharshadi, Elaheh K.
Abstract : The aim of the paper was to investigate the thermal properties of polyethylene (PE)‐clay nanocomposites prepared via the high energy ball milling (HEBM) method. The structure and morphology of the nanocomposites were examined by transmission electron microscopy (TEM), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR). Thermal stability of all milled samples, including pure PE and PE‐clay nanocomposites was measured by thermal gravimetric analysis (TGA). The effect of milling time and clay contents on the thermal stability of PE was investigated. The results show that the thermal stability of PE promotes with increasing milling time. Clay has two opposed functions in the thermal stability of the nanocomposite, the first one is the barrier effect to improve the thermal stability, and another one is the catalysis effect leading to a decrease of the thermal stability. J. VINYL ADDIT. TECHNOL., 22:285–292, 2016. © 2014 Society of Plastics Engineers